Property Price Bubble: Regional Analysis in Indonesia - Kurniawan, Indra; Purwono, Rudi (Universitas Airlangga, 2017)
The aim of this study is to look at the influence of fundamental factors of demand and supply side of the property prices in five major cities in Indonesia using data panel regression methods. In addition, this study analyzes the regional property and the price bubble in Indonesia using the Hodrick Prescott filter analysis. The results of the panel data regression method Showed that the demand-side fundamentals such as economic growth and inflation have a positive effect on property prices as well as interest rate, while the loan to value(LTV) Negatively Affect the price of the property. On the other hand, the fundamental factors of supply-side variable, that is developer's price expectations impact positively the price of the property. HP filter analysis identifying the bubble in every city that lasted for two periods during the study. Keywords: Property Price, Property Price Bubble, Fundamental Factors, Hp Filter JEL: D23, R21, R31